Degree of correspondence between daily monitoring and retrospective recall of alcohol use among men and women with comorbid AUD and PTSD. Issue 2 (29th January 2016) - Krenek, Marketa; Lyons, Robert; Simpson, Tracy L.
Abstract : Background and Objectives: The majority of studies that have identified good correspondence between daily monitoring and retrospective recall of alcohol use have included participants who are relatively stable, are moderate drinkers, report abstinence, and are not diagnosed with comorbid disorders. The current study examined degree of correspondence between alcohol use that was reported daily via interactive voice response (IVR) telephone monitoring and retrospectively using an abbreviated Form‐90 (Form‐35) covering the same 35‐day time period. Methods: Participants were 54 men and women with comorbid alcohol dependence and posttraumatic stress disorder (PTSD) who reported drinking during the time period. Results: Results indicated that participants reported more drinking days via IVR. Correspondence was strong between the reporting methods for aggregate‐level alcohol use variables, including presence/absence of drinking days and heavy drinking days and standard drinks, and associations increased for weeks closer to the assessment date for drinking days and heavy drinking days. Day‐to‐day agreement was moderate for drinking days and heavy drinking days, though there was large between‐person variability in correspondence between reporting methods. Post‐hoc analyzes suggested that men and participants who drink more tend to have lower correspondence between assessment methods. Discussion and Conclusions: Overall, findings partially replicated previous research and extend our knowledge of alcohol assessment in a comorbid sample. Scientific Significance: Findings highlight the importance of considering the influence that moderating variables have on reporting of alcohol use. (Am J Addict 2016;25:145–151)